Основні акценти методики викладання дисциплін зовнішньоекономічного напрямку - Нехай, Вікторія Василівна; Ортіна, Ганна Володимирівна; Плотніченко, Світлана Романівна; Агєєва, Ірина Вікторівна; Вороніна, Юлія Євгенівна; Nekhai, Victoria; Ortina, Hanna; Plotnichenko, Svitlana; Аhieieva, Iryna; Voronina, Yuliia (Запоріжжя : 2024, 2024)
UA: Означено основи та особливості методик викладання дисциплін зовнішньоекономічного блоку відповідно до вимог ринкової та євроінтеграційної спрямованості економіки України. EN: The basics and peculiarities of the teaching methods of economic disciplines, in particular the disciplines of the foreign economic block, the directions of bringing them into line with the requirements of the market and European integration orientation of the economy of Ukraine are defined.
Main accents of the methodology of teaching disciplines in the foreign economic field
Keywords: експортна діяльність; зовнішньоекономічна діяльність; методика викладання; міжнародне право; митна справа export activity; foreign economic activity; teaching method; international law; customs affairs